A Church for a Secular World : The Development of Klaas Schilder's Ecclesiology - Jong, Marinus de (Religious Studies, Theology and Philosophy E-Books Online, Collection 2026., 2025)
The relationship between the Church and the world has been a subject of debate since the Church's earliest days. Stanley Hauerwas, with his emphasis on the Church as polis, has made a significant contemporary contribution-one that has also faced strong criticism. This study examines the distinctive insights of second-generation neo-Calvinist theologian Klaas Schilder (1890-1952) on this issue. Neo-Calvinism is renowned for its development of Reformed theology, particularly in this area, and Schilder builds on this tradition with a critical eye. Engaging with the increasing secularity of the twentieth century, he carefully interacts with Karl Barth's writings while refining his own perspective. In doing so, Schilder's position comes close to the Anabaptist stance of Hauerwas, yet remains firmly rooted in the Reformed understanding of creation.